Metode Pembelajaran Peer Assisted Learning pada Praktikum Anatomi - Saharnauli J. Verawaty Simorangkir (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2015)
Background: Peer Assisted Learning is an active discussion and cooperative learning method within the framework of a partnership in the peer-aged group with the formal structures of the course. PAL is widely seen to be actualised in two modes of operational implementation, which is refer to as “horizontal” and “vertical” peer support. Vertical method was chosen for this research. Method: This research was used causal-comparative design. Tutees for this research was the students of Faculty of Medicine Universitas HKBP Nommensen from batch 2013 who were undergoing block Respiratory System. Tutees were divided into two groups : 24 students in the control group and 25 students in the treatment group. Both of these group consisted of five tutorial groups in which each group consisted of 4-5 students. Whereas the tutor for the treatment group was 5 students from batch 2011. Pre-test and post-test was given to all of the tutees. This research used a questionnaire modified from Clinical Teaching Preference Questionnaire (CTPQ). Results: Pre-test and post-test was analyzed using dependent T-test and Wilcoxon, and the result showed that there were significant enhancement for both of group (p ˂ 0,05). The result from CTPQ indicated most of the students strongly agree that this method was very helpfull in anatomy lab (4,40 ± 0,96). Conclusion: PAL method provided many benefits in learning process including improved social interaction between students and independence in learning.